The eﬀect of adding hip strengthening exercises to lumbar stabilizing exercises on gait for the treatment of non-speciﬁc low back pain: a randomized controlled trial - Mohamed Saleh, Amir; Mahmoud Abdel-Aal, Nabil; Bayuomy Abo Elatta, Ahmed (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. To evaluate the impact of adding hip strength exercises to lumbar stabilizing exercises on pain, disability, and spatio-temporal parameters of gait in the treatment of non-speciﬁc low back pain (NSLBP).Methods. In this randomized controlled trial, 60 patients diagnosed with NSLBP were randomized into two equal groups. The subjects were randomly allocated to either group A, the control group (n = 30), performing lumbar stabilizing exercises, or group B, the study group (n = 30), receiving lumbar stabilizing exercises and a progressive hip strengthening exercise program. The frequency of intervention was 3 sessions per week for six weeks. In this trial, the Visual Analogue Scale for pain intensity, Modiﬁed Oswestry Disability Index for disability, and Kinovea 2D motion analysis for spatio-temporal parameters were evalu-ated pre-treatment and after six weeks.Results. There were statistically signiﬁcant diﬀerences between groups in changes in pain scores (p = 0.035), the disability index (p = 0.012), and COG vertical displacement (p = 0.017). There were no statistically signiﬁcant diﬀerences in stride length, stride time, stride speed, or cadence between the control and study groups (p > 0.005).Conclusions. Adding hip strengthening exercises to a lumbar stabilization exercise program can reduce pain and disability and decrease COG vertical displacement more than a lumbar stabilization exercise program alone in NSLBP patients. However, no diﬀerences were found in gait speed, cadence, stride length, and stride time.
Keywords: non-speciﬁc low back pain; Kinovea; hip strengthening exercises; lumbar stabilization exercises